From Erotic Verse to Sacred Word: Binhad Nurrohmat's Poetic Pilgrimage Through Prophetic Structuralism for Character Education and SDG 4 - Akhmad Fatoni; Darni Darni; Anas Ahmadi; Khuaxay Sengsouk; Silva Anggi Lestari (Journal of Current Studies in SDGs, 2026)
Objective: To explore the poetic transformation of Binhad Nurrohmat from his urban Jakarta period to his spiritually contemplative works in Javanese pesantren culture. It seeks to understand how this poetic shift reconfigures the relationship between literary practice, ethical subjectivity, and spiritual transcendence. Method: The research uses prophetic structuralism, a theoretical synthesis of Pierre Bourdieu's sociology of cultural production (habitus, field, capital) and Kuntowijoyo's Islamic prophetic paradigm (humanization, liberation, transcendence). Data were collected through close reading of Nurrohmat's selected poetry collections published between 2014 and 2021, as well as contextual analysis of his biographical trajectory from Jakarta to Jombang. Results: The findings reveal that Nurrohmat's work embodies a tripartite movement within prophetic structuralism, comprising Amil, Amal, and Amul. First, in the Amil dimension, the poet positions himself as an ethical subject situated between the secular and the sacred realms. Second, in the Amal dimension, poetry functions as a critical social practice. Third, in the Amul dimension, language becomes a medium of contemplative transcendence. The pesantren functions not merely as a backdrop but as a transformative field that reshapes poetic habitus and spiritual capital. Novelty: Contributing prophetic structuralism as a new theoretical framework for analyzing Islamic literature, moving beyond thematic interpretation to integrate authorial habitus, field dynamics, and spiritual capital. It offers a broader reflection on Islamic literary modernity that engages deeply with tradition while performing a critical, spiritually infused aesthetics relevant to post-secular literary discourse and SDG 4 (Quality Education), particularly target 4.7 on education for sustainable development.